Bioethics and Human Rights. - Sgreccia, Elio; Casini, Marina (Medicina e Morale, 1999)
Is there a connection between bioethics and human rights? The article, starting from this question and going through a detailed analysis, comes to the conclusion that a pure and clear acknowledgment of any human being's dignity and right to life from conception is what bioethics actually shares with research on human rights. The two disciplines also require such an acknowledgment to avoid the individualistic diversions of utilitarianism and of ethical relativism. The analysis of the relationship between bioethics and human rights has two historical starting points, namely the Nuremberg Trial and the Universal Declaration of Human Rights, which both represented a change in the human course of events. The new stream in bioethics was the "normative-legal" one, which throughout the years would assume more and more relevance, until it resulted in an independent research field known as "bio-law". With regard to this, this article offers an ethical investigation among the main national and international legal documents which deal with "bioethical issues". As a result, the need of integration between human rights and bioethics, on the one side, and the urgency of giving them solid and genuine foundations, on the other one, are admitted. This is indeed a crucial problem, since both human rights and bioethics suffer a metaphysical crisis, which is particularly evident and cruel with respect to the weakest human life situations, when life just "is". In this sense, human embryo is the symbol of any poverty and social marginalization. An escape from this crisis - as well as a true search for human rights and bioethics foundations - can be found in the human dignity perspective. Human dignity always belongs to anyone with the same strength and vehemence, therefore it needs respect and support through such principles as the right to life, which is the primary manifestation and actualization of dignity.